Examining the Implications of Dual Roles of Manufacturers - Parthasarathy, Yuvaraj (2011)
Abstract The focus of this research is in the area of a manufacturing industry’s implications that acts as the second tier supplier to the Western Business & as first tier collaborative partner to the business in their own country and also provides specific quality of products to the internal markets and differentiated quality of products to the western markets. In this research initially the main focus was made on the Indian Manufacturing Industries on the literature review, which provides the export details of various Indian manufacturing sectors to the external market. The detailed description was provided on the technology status, factors in technological competitiveness, R&D and technology development initiatives of Indian Manufacturing Industries. And also elaborated explanation is done on the concepts on Supply Chain Management, Manufacturing Strategy and Focused Manufacturing. The analysis approach in this dissertation is done by visiting an Indian manufacturing industry that plays dual roles in manufacturing and conducting interviews with the company officials. Interviewing the company’s officials in their industry gained in collecting information on their business model, organisational theory, infrastructure capabilities, supply chain relationships and their implications of playing dual roles in manufacturing. Even the conflicts faced by the company are examined in this research. The main conclusions drawn from this study illustrates the issues on several aspects on providing different quality of products for the domestic & foreign market and recommendations are outlined which would help in enhancing the dual roles of manufacturer to solve the conflicts in both the markets.